THE ISSUES WITH MODERN ENGLISH TEACHING METHODS IN UNIVERSITIES (American Journal of Pedagogical and Educational Research, 2024)
The issues with different approaches to teaching foreign languages in universities are discussed in the essay. The direct method, grammar-translation, audiovisual, audio-lingual, and communicative approaches all received special attention. Modern teaching methods, according to the author, involve the application of such a system of procedures, which are intended to help trainees master knowledge independently through active cognitive activity rather than to replicate the teacher's ready-made knowledge presentations.